Experimental study on cooling performance of 3D printed tapered conformal channel - Lim, Bernard Wei Xuan (Nanyang Technological University, 2021)
Selective Laser Melting (SLM) has been widely used for the production of subtle metal components in many different industries due to its dramatic efficiency and eco-friendly processing. In addition, SLM can fabricate complex structures which cannot be fabricated by traditional manufacturing methods. A good example of such complex structures which can be manufactured using SLM is the smart plastic injection mould. A conformal cooling channel is integrated into these moulds to improve the performance by providing better cooling uniformity and reducing the cooling time required. This final year report presents the experimental study of the various parameters affecting the effectiveness of a conformal cooling channel. In this study, I proposed to use a circulate channel with a tapered section to increase the internal surface area to increase cooling efficiency. The mould was first designed using Computer-Aided Design (CAD) software then manufactured using the SLM process. Afterwards, experiments were conducted to test the mould performance by changing the flow rate to see the effect it has on the heat transfer rate. Four different cooling water flow rates, 0.1 L/min, 0.2 L/min, 0.3 L/min and 0.4L/min were used in the experiments conducted. In the end, it was concluded that by increasing the flow rate of the coolant flowing in the channel, the cooling performance will increase by up to 17%. However, there is a small drawback as the pressure required increases due to a larger pressure drop. Future work can be done by altering the design parameters of the current conformal cooling channel or even exploring a different type of structure and testing their cooling performance. By doing so, we will be able to better understand the effects of changing certain design parameters and finding an optimum conformal cooling channel design that would produce the least cooling time needed with a high cooling uniformity for an injection moulding process.